Cashew (Anacardium occidentale L.) Nuts Counteract Oxidative Stress and Inflammation in an Acute Experimental Model of Carrageenan-Induced Paw Edema - Marika Cordaro; Rosalba Siracusa; Roberta Fusco; Ramona D'Amico; Alessio Filippo Peritore; Enrico Gugliandolo; Tiziana Genovese; Maria Scuto; Rosalia Crupi; Giuseppina Mandalari; Salvatore Cuzzocrea; Rosanna Di Paola; et al. (MDPI AG, 2020)
Background: Anacardium occidentale L. is a medicinal plant with powerful anti-oxidative and anti-inflammatory properties. Acute inflammatory events cause tissue alterations, decrease of anti-oxidative endogenous enzymes such as superoxide dismutase, catalase and glutathione, neutrophils infiltration, increase in the activities of myeloperoxidase, malondialdehyde, and pro-inflammatory release. Methods: Paw edema was induced by subplantar injection of carrageenan into the right hind paw in rats, but 30 min before a group of animals were orally treated with 100 mg/kg of cashew nuts to evaluate the anti-inflammatory and anti-oxidative response. Results: In the present work, we found that (1) cashew nuts reduced the development of carrageenan-induced paw edema limiting the formation of edema and pain; (2) cashew nuts ameliorated the diminutions of the anti-oxidative enzymes caused by carrageenan injection; (3) cashew nuts decreased myeloperoxidase malondialdehyde activity induced by carrageenan; and (4) cashew nuts acted by blocking pro-inflammatory cytokines response and nitrate/nitrite formation stimulated by carrageenan injection. Conclusions: The mechanisms of anti-inflammatory and analgesic effects exerted by cashew nuts were relevant to oxygen free radical scavenging, anti-lipid peroxidation, and inhibition of the formation of inflammatory cytokines.